Tips for Maintaining Philanthropic Motivation in a Social Institution During a Pandemic - Almagribi, Ahmad Bilal; Muslimah, Muslimah; Erawati, Desi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
This study aims to explore information about tips by philanthropists in maintaining their philanthropic motivation during the COVID-19 pandemic, conditions that are burdensome for philanthropy, the intensity of philanthropy, and how they invite others to philanthropy. This study uses a qualitative approach with data collection methods in the form of observation, interviews, open questionnaires, and documentation. The analysis was carried out using data triangulation techniques. The results showed that some of their main tips in maintaining their philanthropic motivation were: a strong commitment to sharing sustenance, believing that alms can keep away all problems, philanthropy has become a necessity and joining alms management groups. Conditions or things that have the potential to burden philanthropists: when there is an urgent need, when income is decreasing, the location is remote, and when the institution is no longer trustworthy. The majority of philanthropy levels remain even during the pandemic. As for how to invite others to do philanthropy, such as inviting them directly together, explaining the virtues of alms including through social media, giving examples of philanthropy, distributing brochures and orphanage calendars.